Variations in Microcredit Interest Rates - Kneiding, Christoph; Rosenberg, Richard (World Bank, Washington, DC, 2012)
Global differences in microcredit interest rates are dramatic. The global average is about 35 percent, but the average in Uzbekistan is above 80 percent, and in Sri Lanka it is around 17 percent. Small loan sizes are the most commonly cited reason why microcredit rates are higher than normal bank rates. Microcredit is a "high-touch" business, and microfinance institutions (MFIs) have to process thousands of tiny transactions. Apparently, there is no single, simple explanation for the considerable inter-country differences in interest rates. In addition to small loan sizes, which undoubtedly are an important driver behind interest rates, other dynamics are at work. This current research has already started to address some fundamental questions: 1) how do borrowers comparably fare in low-interest and high-interest environments? 2) What is the effect of competition on MFIs' efficiency? Does more competition necessarily lead to lower interest rates? 3) How should public policy exert influence on the domestic microfinance sector? What are the features of an "appropriate" regulatory environment?